KEBIJAKAN PENGELOLAAN HUTAN ADAT PASCA PUTUSAN MAHKAMAH KONSTITUSI NO. 35/PUU-X/2012: SUATU TINJAUAN KRITIS - Subarudi Subarudi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Existency of customary law people (MHA) has been marginalized under the state authority. However, this authority ends through Constitutional Court (MK) decision No. 35/2012 that stated customary forest (CF) is not under the state forest. This paper is to review CF at post MK decision with objectives: 1) to give definition of customary people (MA) and MHA; 2) to identify regulations related to CF management; 3) to asess the impact of MK decision on the revision of Forestry Law No. 41/1999 and 4) to formulate strategies for future CF management. This review used political economy approach and qualitative descriptive analysis. Result of the review indicated that there is no different between the term of MA and MHA due to their same definition. Eight laws involved in definition and rights of MHA, however, their contents and implementation are different depending on sectoral perceptions. The MK Decree No. 35 has significant impact on forest management with the exlusion of CF from the state forest and not included in the (private) right forest. A strategy for future CF management is the full joint commitment among governments, NGOs and MHA itself related to MHA determination, territorial boundary of CF and establishment of customary institutional system.